Systematic Assessment of Human CCR7 Signalling Using NanoBRET Biosensors Points towards the Importance of the Cellular Context - Nathan Vanalken; Katrijn Boon; Martyna Szpakowska; Andy Chevigné; Dominique Schols; Tom Van Loy (Biosensors, 2024)
The human CC chemokine receptor 7 (CCR7) is activated by two natural ligands, CC chemokine ligand 19 (CCL19) and 21 (CCL21). The CCL19-CCL21-CCR7 axis has been extensively studied in vitro, but there is still debate over whether CCL21 is an overall weaker agonist or if the axis displays biased signalling. In this study, we performed a systematic analysis at the transducer level using NanoBRET-based methodologies in three commonly used cellular backgrounds to evaluate pathway and ligand preferences, as well as ligand bias and the influence of the cellular system thereon. We found that both CCL19 and CCL21 activated all cognate G proteins and some non-cognate couplings in a cell-type-dependent manner. Both ligands recruited β-arrestin1 and 2, but the potency was strongly dependent on the cellular system. Overall, CCL19 and CCL21 showed largely conserved pathway preferences, but small differences were detected. However, these differences only consolidated in a weak ligand bias. Together, these data suggest that CCL19 and CCL21 share mostly overlapping, weakly biased, transducer profiles, which can be influenced by the cellular context.